Researchers experience of using the regulatory affairs information system (RAIS) in strengthening research compliance in a large research program: A case study of the Infectious Diseases Institute (IDI) in Uganda. Issue 3 (14th July 2022) - Nabukenya, Sylvia; Okoboi, Stephen; Nakate, Vivian; Twimukye, Adelline; Opio, Bruce; Castelnuovo, Barbara
Abstract: Objective: The aim of this study was to explore researchers' experience of using the regulatory affairs information system (RAIS) in strengthening research compliance to national ethics guidelines through tracking ethics and regulatory approvals for research projects at the Infectious Diseases Institute. Methods: We conducted a cross-sectional study using purposive sampling of 50 participants who were principal investigators (PI) and study coordinators (SC) of active projects between November 2019 and January 2020. Only 36 of them responded to the survey. We also conducted 12 key informant interviews among PI, SC, and research management at the Institute. We used STATA 13 to analyze responses to the survey. The interviews lasted between 20 and 30 min. We used NVivo 10 software to manage the transcripts and generation of themes. Results: Majority 19 (52.8%) of those who participated in the survey were study coordinators, 19 (52.8%) had participated in more than 5 research studies, 28 (90.3%) had ever received a notification from the RAIS and 26 (92.9%) submitted requests for renewal of their studies approvals to Ethics committees and regulatory bodies 4 weeks prior to expiration dates. The study also examined participants' general understanding of the regulatory requirements and all were aware that RECs and NDA grant approval for a period of 1 year, and 35 (97.2%) that UNCST grants approval for the duration of the study. Three prominent themes; researchers' experiences, benefits, and shortcomings of RAIS were generated from the key informant interviews. Discussion: Having experience in research coupled with a novel automated system provides a platform for a better understanding of research regulatory requirements, hence compliance to the national guidelines. Conclusion: Our case study demonstrates that supporting researchers and research institutions in low resource settings with an automated system in tracking expiration dates for research approvals can facilitate compliance to national ethics guidelines. Lay Summary: Several standards and regulations have been developed to guide researchers' conduct of research procedures to protect participants' rights, safety, and welfare. However, compliance to all ethical guidelines is sometimes difficult given the workload researchers have to carry to meet the proposed objectives. This study aimed at exploring researchers' experience of using the regulatory affairs information system (RAIS) in strengthening research compliance to national ethics guidelines.This study employed both quantitative and qualitative methods between November 2019 and January 2020. Thirty-six participants responded to the online survey, which comprised questions related to socio-demographics and usage of the RAIS in supporting compliance to national research guidelines. The study also examined participants' general understanding of the regulatory requirements and all were aware that RECs and NDA grant approval for a period of 1 year, and 35 (97.2%) that UNCST grants approval for the duration of the study. Twelve participated in the key informant interviews. Three prominent themes; researchers' experiences of using the RAIS in tracking expiration dates for Research ethics committees (RECs) or Uganda National Council for Science and Technology (UNCST) or National Drug Authority (NDA) approvals, benefits of the RAIS database, and shortcomings of RAIS were generated from the key informant interviews.Our study demonstrates that supporting researchers and research institutions in low resource settings with an automated regulatory system in tracking expiration dates for ethics committees and regulatory bodies' approvals can facilitate compliance to guidelines for research involving human participants.